Introducing Trifluoromethyl to Strengthen Hydrogen Bond for High Efficiency Organic Solar Cells - Zhang, Hao; Du, Xiaoyang; Tang, Yunhan; Lu, Xi; Zhou, Lei; Zheng, Caijun; Lin, Hui; Tao, Silu (Frontiers in Chemistry, 2020)
Nowadays, the ternary strategy has become a common way to improve the power conversion eﬃciency (PCE) of organic solar cells (OSCs). The intermolecular interaction between the third component and donor or acceptor plays a key role in achieving a high performance. However, hydrogen bond as a strong intermolecular interaction is rarely considered in ternary OSCs. In this work, we introduce trifluoromethyl on a newly synthesized small molecular DTBO to strength hydrogen bonds between DTBO and IEICO-4F. Due to the existence of hydrogen bonds has a strong impact on electrostatic potential (ESP) and benefits π-π stacking in the active layer, the ternary OSCs show superior charge extraction and low charge recombination. In DTBO, PTB7-Th and IEICO-4F based ternary devices, the PCE increases from 11.02% to 12.48%, and short-circuit current density (JSC) increases from 24.94 mA/cm2 to 26.43 mA/cm2 compared with typical binary devices. Moreover, the addition of DTBO can realize an energy transfer from DTBO to PTB7-Th and broaden the absorption spectrum of blend films. Grazing-incidence wide-angle X-ray scattering (GIWAXS) patterns show that the π-π stacking distance of IEICO-4F decreased after adding 10wt% DTBO. The effect of the hydrogen bond is also achieved in the PM6: Y6 system, showing 16.64% efficiency by comparison to the 15.49% efficiency of binary system. This work demonstrates that introduce trifluoromethyl to enhance hydrogen bond which improve π-π stacking can achieve higher performance in OSCs.